Cambodias new technical and vocational education and training policy. - Ebener, Steeve (ADB Briefs., 2018)
This issue summarizes Cambodias new Technical and Vocational Education and Training (TVET) Policy 2017 to the policy among the wide range of TVET stakeholders including ministries, training institutions, employer and employee associations, development partners, civil society organizations, and Cambodias youth. The new policy will guide the formulation and implementation of strategies for skills development and will facilitate better coordination among those involved in skills development in Cambodia. The policy was developed through a consultative process with technical assistance from ADB with the goal of transforming and modernizing Cambodias skills development system to better serve new labor force entrants, existing workers, and Cambodias future development.